Pengaruh Budaya Organisasi Dan Employee Engagemen Terhadap Kinerja Pegawai Pada Dinas Kebudayaan Dan Pariwisata Kabupaten Toraja Utara - Christian Y Rumissing; Althon K. Pongtuluran; Adriana Madya Marampa (Journal Of Business, Finance, and Economics (JBFE), 2024)
The Influence of Organizational Culture and Employee Engagement on Employee Performance at the North Toraja Regency Culture and Tourism Service. This research aims to determine the influence of organizational culture and employee engagement on employee performance at the North Toraja Regency Culture and Tourism Service. The object of this research is the North Toraja Regency Culture and Tourism Service. This research uses a quantitative approach with multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 26 application. The population in this research is employees at the North Toraja Regency Culture and Tourism Service. as many as 30 respondents. This research shows that Organizational Culture and Employee Engagement both have a positive and significant effect on performance. By testing the coefficient of determination, a value of 0.602 or 60.2% was obtained. The Performance variable can be explained by the Organizational Culture and Employee Engagement variables while the remaining 30.8% is explained by other variables.